Enhancing Independent Learning Competence through Digital Technologies in Teaching English to Philology Students - Azzamov, Yusuf (The Lingua Spectrum, 2025)
This article provides a theoretical and practical analysis of the role of digital technologies in forming and improving independent learning competence among philology students during the process of mastering the English language. The paper highlights the opportunities of the digital learning environment for managing students’ independent study activities, self-assessment, reflection, and cognitive engagement. According to the research findings, the digitally integrated methodological model increased philology students’ independent learning competence by 25-35 percent. Furthermore, a four-stage learning model developed on the basis of modern digital platforms (Moodle, Google Classroom, ChatGPT, Quizlet, Duolingo) is presented. The results are compared with international approaches such as constructivism, the reflective cycle, and competence-based education.